2009
DOI: 10.1007/s10393-009-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing Mechanisms of the Dilution Effect: Deer Mice Encounter Rates, Sin Nombre Virus Prevalence and Species Diversity

Abstract: Species diversity has been shown to decrease prevalence of disease in a variety of host-pathogen systems, in a phenomenon termed the Dilution Effect. Several mechanisms have been proposed by which diversity may decrease prevalence, though few have been tested in natural host-pathogen systems. We investigated the mechanisms by which diversity influenced the prevalence of Sin Nombre virus (SNV), a directly transmitted virus in deer mice (Peromyscus maniculatus). We monitored both intra and interspecific encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 33 publications
3
56
0
1
Order By: Relevance
“…Since then, several studies using simulation models, and experimental and empirical data, have revealed details of this mechanism of disease regulation (Ostfeld and Keesing 2000;Ostfeld and LoGiudice 2003;Keesing et al 2010). More recently, this effect was also confirmed to explain the prevalence of other diseases, such as the West Nile virus (Ezenwa et al 2006;Swaddle and Calos 2008;Allan et al 2009), hantavirus (Clay et al 2009;Suzán et al 2009), and schistosomiasis (Johnson et al 2009). …”
Section: Introductionmentioning
confidence: 82%
“…Since then, several studies using simulation models, and experimental and empirical data, have revealed details of this mechanism of disease regulation (Ostfeld and Keesing 2000;Ostfeld and LoGiudice 2003;Keesing et al 2010). More recently, this effect was also confirmed to explain the prevalence of other diseases, such as the West Nile virus (Ezenwa et al 2006;Swaddle and Calos 2008;Allan et al 2009), hantavirus (Clay et al 2009;Suzán et al 2009), and schistosomiasis (Johnson et al 2009). …”
Section: Introductionmentioning
confidence: 82%
“…16 The change in ecological processes as a result of anthropogenic actions puts pressure on the natural environment, increasing the risk of human contact with pathogens, many of which can be transmitted by mosquitoes (Bradley and Altizer, 2007). It has been demonstrated that loss of diversity tends to increase pathogens transmission incidence of diseases such as malaria, West Nile Fever (WNF), schistossomose, Lyme disease and hantavirus (Ezenwa et al, 2006;LoGuidice et al, 2008;Clay et al, 2009;Johnson et al, 2009, Laporta et al, 2013. Therefore,the policy makers should propose the creation and maintenance of green areas aimed mainly at conserving ecosystems and natural communities, thus reducing the risk of pathogen transmission.…”
Section: Discussionmentioning
confidence: 98%
“…All of these metrics are routinely used in examining diversity-disease relationships, but multiple metrics are rarely reported. 10,18,22,[67][68][69] An important area for future research that will help extend the reach of these observations will be learning more about interactions between rodent communities in agricultural and conserved sites. All of the rodent species found in agricultural sites were also detected in paired conserved sites.…”
Section: Discussionmentioning
confidence: 99%